Watch the target! Effects in the affective misattribution procedure become weaker (but not eliminated) when participants are motivated to provide accurate responses to the target - Eder, Andreas B.; Deutsch, Roland (Frontiers in Psychology, 2015)
Previous research showed that priming effects in the affective misattribution procedure (AMP) are unaffected by direct warnings to avoid an influence of the primes. The present research examined whether a priming influence is diminished by task procedures that encourage accurate judgments of the targets. Participants were motivated to categorize the affective meaning of nonsense targets accurately by being made to believe that a true word was presented in each trial and by providing feedback on (allegedly) incorrect responses. This condition produced robust priming effects. Priming was however reduced and less reliable relative to more typical AMP conditions in which participants guessed the meaning of openly presented nonsense targets. Affective judgments of nonsense targets were not affected by advance knowledge of the response mapping during the priming phase, which argues against a response-priming explanation of AMP effects. These findings show that affective primes influence evaluative judgments even in conditions in which the motivation to provide accurate responses is high and a priming of motor responses is not possible. Priming effects were however weaker with high accuracy motivation, suggesting that a focus on accurate judgments is an effective strategy to control for an unwanted priming influence in the AMP.